Spreadsheet Comprehension: Guesswork, Giving up and Going back to the Author - Srinivasa Ragavan, Sruti; Sarkar, Advait; Gordon, Andy (CHI '21: Proceedings of the 2021 CHI Conference on Human Factors in Computing Systems, 2021)
Spreadsheet users routinely read, and misread, others' spreadsheets, but literature offers only a high-level understanding of users’ comprehension behaviors. This limits our ability to support millions of users in spreadsheet comprehension activities. Therefore, we conducted a think-aloud study of 15 spreadsheet users who read others’ spreadsheets as part of their work. With qualitative coding of participants’ comprehension needs, strategies and difficulties at 20-second granularity, our study provides the most detailed understanding of spreadsheet comprehension to date. Participants comprehending spreadsheets spent 40% of their time seeking additional information needed to understand the spreadsheet. These information seeking episodes were tedious: 50% of participants reported feeling overwhelmed. Moreover, participants often failed to obtain the necessary information and worked with guesses about the spreadsheet instead. Eventually, 12 out of 15 participants decided to go back to the spreadsheet’s author for clarifications. There are tool implications for reading as well as writing spreadsheets.